World health Organization’s guidance for tracking non-communicable diseases towards sustainable development goals 3.4: an initiative for facility-based monitoringResearch in context - Arlene Quiambao; Mohammad-Reza Malekpour; Ali Golestani; Mahsa Heidari-Foroozan; Seyyed-Hadi Ghamari; Mohsen Abbasi-Kangevari; Benjamin O. Anderson; Prebo Barango; Elena Fidarova; Bianca Hemmingsen; Andre Ilbawi; Taskeen Khan; et al. (EClinicalMedicine)
Summary: Background: Non-communicable diseases (NCDs) account for over 60% of annual global deaths, disproportionately affecting low- and middle-income countries. This trend undermines progress toward Sustainable Development Goal (SDG) 3.4, which seeks to reduce premature mortality from NCDs by one-third by 2030. Despite the availability of effective and relatively affordable interventions, addressing NCDs requires sustained, coordinated efforts and robust monitoring systems. Facility-based monitoring offers a dynamic alternative to static surveys, enabling continuous assessment of healthcare quality and utilization. Methods: This study followed a systematic approach to develop standardized global and national NCD monitoring indicators, using the Donabedian model as a conceptual framework. It focused on four major NCD categories: hypertension and cardiovascular diseases (CVDs), diabetes, chronic respiratory diseases, and cancers. The methodology included systematic scoping reviews from inception up to November 2021 and a multi-round Delphi process involving global experts to assess the validity and feasibility of proposed indicators. This study was funded internally by WHO. There were no payments to participants. Findings: The final output consisted of 81 validated indicators—22 core and 59 optional. These indicators demonstrated high feasibility and relevance for facility-based monitoring of NCD service delivery. They provide actionable metrics for assessing and improving the quality of care across diverse health system settings. Interpretation: This study highlights the urgent need for comprehensive, context-sensitive NCD monitoring frameworks. The proposed set of indicators offers a validated foundation for improving NCD care delivery and aligns with efforts to achieve SDG target 3.4. Ongoing updates and local adaptations will be essential to ensure continued relevance and effectiveness. Funding: This study was funded internally by WHO.